E-Marketing Bagi Pelaku UMKM Di Desa Citeras Kec. Rangkasbitung Kab.Lebak-Banten - Miguna Astuti; Tati Handayani (Universitas Serang Raya, 2020)
This study aims to carry out community service activities (ABDIMAS) to provide knowledge of e-marketing so that participants are able to recognize, understand and apply e-marketing in marketing their products so that they can advance their business. There are 67 micro, small and household craft industries in Citeras village, but their e-marketing activities did not reach 5%. The method of this ABDIMAS activity is a participatory method through training and mentoring activities where the implementation is evaluated using questionnaires and measured based on the criteria and indicators that have been made and the service team provides pocketbooks for deeper guidance. The results of this service are (1) a high level of participation from the Citeras village office and communities that have MSME businesses that fully support the Community Partnership Program. This can be seen from the willingness of the village to facilitate the event and also be seen from the enthusiastic arrival of the participants during training and mentoring.(2) All participants of the Community Partnership Program stated that the Community Partnership Program activities were very beneficial for their business and some of them hoped that the Community Partnership Program activities would be carried out routinely with the same material, especially in the mentoring section (APPLICATION).